Detectability and surgical outcomes in parathyroid surgery – a single-centre experience. Issue 4 (May 2019) - Borumandi, F.; Daultrey, H.; Laji, K.; Bosman, D.; Ashford, N.; Alam, P.
Abstract: The incidence of primary hyperparathyroidismand referrals for the removal of parathyroid adenomas are increasing. Factors that improve the detectability, and ultimately the surgical outcome, are the focus of this retrospective study. We included 117 patients who had parathyroid operations with intraoperative monitoring of parathyroid hormone (PTH). Sestamibi, ultrasound and, in selected cases, fusion with computed tomograms (CT), were done to locate the lesion preoperatively. Concentrations of calcium and PTH before and after operation, specimen weight, and preoperative vitamin D concentrations, were assessed. The sensitivity of sestamibi and ultrasound for the preoperative location of adenomas was 92% and 80%, respectively. Sestamibi located them more accurately in patients with low preoperative concentrations of vitamin D (p = 0.037) and with heavier adenomas (p < 0.001). We found no significant association between the preoperative concentrations of PTH and detectability on preoperative scans (p = 0.058). Postoperative follow up showed that 97% of the 117 patients were biochemically cured. Accurate location helps to lower morbidity as it facilitates a targeted approach. Further studies are needed to explore the role of vitamin D in the location of parathyroid adenomas before parathyroidectomy.